The Unequal Pandemic : COVID-19 and Health Inequalities - Bambra, C. (Clare); Smith, Katherine E.; Lynch, Julia, 1970- (Book collections on Project MUSE., 2021)
This accessible, yet authoritative book shows how the pandemic is a syndemic of disease and inequality. Drawing on international data and accounts, it argues that these inequalities are a political choice and we need to learn quickly to prevent growing inequality and to reduce health inequalities in the future.